Synthesis and Characterization of Some Transition Metal Complexes of 2-Naphthoin Oxime - Mehta, B.H.; Nagarkoti, B.S. (Asian Journal of Chemistry, 2010)
Transition metal complexes of 2-naphthoin oxime have been synthesized and characterized by elemental analysis, molar conductance, and magnetic and spectral data. Various bonding features were established on the basis of IR spectral data. The electronic spectral data are calculated. The structural geometry is assigned on the basis of various spectral findings.